Ligand-Mediated Biofilm Formation via Enhanced Physical Interaction between a Diguanylate Cyclase and Its Receptor - David Giacalone (American Society for Microbiology, 2018)
ABSTRACT The bacterial intracellular second messenger, cyclic dimeric GMP (c-di-GMP), regulates biofilm formation for many bacteria. The binding of c-di-GMP by the inner membrane protein LapD controls biofilm formation, and the LapD receptor is central to a complex network of c-di-GMP-mediated biofilm formation. In this study, we examine how c-di-GMP signaling specificity by a diguanylate cyclase (DGC), GcbC, is achieved via interactions with the LapD receptor and by small ligand sensing via GcbC’s calcium channel chemotaxis (CACHE) domain. We provide evidence that biofilm formation is stimulated by the environmentally relevant organic acid citrate (and a related compound, isocitrate) in a GcbC-dependent manner through enhanced GcbC-LapD interaction, which results in increased LapA localization to the cell surface. Furthermore, GcbC shows little ability to synthesize c-di-GMP in isolation. However, when LapD is present, GcbC activity is significantly enhanced (~8-fold), indicating that engaging the LapD receptor stimulates the activity of this DGC; citrate-enhanced GcbC-LapD interaction further stimulates c-di-GMP synthesis. We propose that the I-site of GcbC serves two roles beyond allosteric control of this enzyme: promoting GcbC-LapD interaction and stabilizing the active conformation of GcbC in the GcbC-LapD complex. Finally, given that LapD can interact with a dozen different DGCs of Pseudomonas fluorescens, many of which have ligand-binding domains, the ligand-mediated enhanced signaling via LapD-GcbC interaction described here is likely a conserved mechanism of signaling in this network. Consistent with this idea, we identify a second example of ligand-mediated enhancement of DGC-LapD interaction that promotes biofilm formation. IMPORTANCE In many bacteria, dozens of enzymes produce the dinucleotide signal c-di-GMP; however, it is unclear how undesired cross talk is mitigated in the context of this soluble signal and how c-di-GMP signaling is regulated by environmental inputs. We demonstrate that GcbC, a DGC, shows little ability to synthesize c-di-GMP in the absence of its cognate receptor LapD; GcbC-LapD interaction enhances c-di-GMP synthesis by GcbC, likely mediated by the I-site of GcbC. We further show evidence for a ligand-mediated mechanism of signaling specificity via increased physical interaction of a DGC with its cognate receptor. We envision a scenario wherein a “cloud” of weakly active DGCs can increase their activity by specific interaction with their receptor in response to appropriate environmental signals, concomitantly boosting c-di-GMP production, ligand-specific signaling, and biofilm formation.